Study for determination of the optimal cessation period of therapy with anti-platelet agents prior to invasive endoscopic procedures - Komatsu, Tomoko; Tamai, Yoshiko; Takami, Hideki; Yamagata, Kazufumi; Fukuda, Shinsaku; Munakata, Akihiro (Journal of gastroenterology, 2005)
Anti-platelet agents are widely used for the treatment and prevention of thrombotic diseases. On the other hand, continuation of anti-platelet agents increases the risk of hemorrhagic complications in gastrointestinal endoscopy, and cessation of anti-platelet agents exposes the patient to the risk of thromboembolism. Only a few studies have actually studied the whether a cessation period is required prior to endoscopic procedures and if so, the optional duration of the period. The present study assessed the time course of primary hemostasis after the cessation of anti-platelet agents. Eleven healthy men (age range, 19-29 years) were assigned to each of the following regimens: aspirin (ASA; 100 mg/day), ticlopidine (TP; 300 mg/day), and a combination of ASA (100 mg/day) and TP (300 mg/day) for 7 days. There was a washout period of more than 3 weeks between each regimen. A quantitative bleeding time test (QBT test) and platelet aggregation test were performed before the beginning of administration, on the last day of administration, and at 1, 3, and 5 days after cessation, and also at 7 days after cessation for the combination regimen. The average bleeding time (BT) and total bleeding loss volume (Tv) of the 11 subjects after administration of the three regimens were significantly increased compared with those before administration. With the administration of ASA, increases of BT and Tv at 3 days after cessation were not significant. The Tv at 5 days after cessation of TP was not significantly increased. With the combination regimen, the BT and Tv at 7 days after cessation were not significantly increased. A 3-day cessation period for ASA, a 5-day cessation period for TP, and a 7-day cessation period for ASA+TP administration seem to be sufficient.